Characterization of granular phase change materials for thermal energy storage applications in fluidized beds. (1st November 2016) - Izquierdo-Barrientos, M.A.; Sobrino, C.; Almendros-Ibáñez, J.A.; Barreneche, C.; Ellis, N.; Cabeza, L.F.
Highlights: Granular PCMs are tested in 3D and 2D fluidized beds. Density, particle size and angle of repose were measured for different granular PCMs. DSC measurements confirm that there is no loss of material after fluidization. Abstract: This work investigates commercially available granular phase change materials (PCMs) with different transition temperatures for the use of thermal-energy storage systems in fluidized beds. The hydrodynamic characteristics of granular PCMs were tested in cylindrical-3D and planar-2D fluidized beds. The density, particle size distribution and angle of repose were measured for various PCM materials. Further attrition studies were conducted with changes in particle surface from abrasion, which were characterized using a Scanning Electron Microscope (SEM). The results indicate that some materials with smaller particle size and thinner supporting structure can lose the paraffin during the fluidization process, when paraffin is in a liquid state. As a consequence, the particles agglomerate, and the bed defluidizes. For all of the tested materials, only GR50 (with a transition temperature of 50 °C) properly fluidizes when the paraffin is in the liquid state and has shown to endure >75 h of continuous operation and 15 melting-solidification cycles in a fluidized bed. Additional differential scanning calorimetry (DSC) measurements of the cycled particles did not show a decrease in energy storage capacity of the granular PCM, which corroborates that there is no loss of material after >75 h of fluidization.